Nasal Adenocarcinoma in a Horse with Metastasis to Lung, Liver, and Bone and Review of Metastasis in Nine Horses with Sinonasal Tumors - Ashley Hanna; Susanne M. Stieger-Vanegas; Jerry R. Heidel; Melissa Esser; John Schlipf; Jacob Mecham (Case Reports in Veterinary Medicine)
Sinonasal neoplasia metastasizing to distant organs is rare in horses. This case report describes the clinical and imaging findings of a horse with sinonasal neoplasia, which had metastasized to the lung, liver, and humerus. Additionally, the prevalence of sinonasal neoplasia and their incidence of distant metastasis among horses that presented to the Oregon State University Veterinary Teaching Hospital (OSU-VTH) were estimated. Of 5,558 equine patients who presented to the OSU-VTH in the last nine years, 1.4% were diagnosed with sinonasal disease and 10.3% of these cases had sinonasal neoplasia with only one having confirmed distant metastasis. This case was an eleven-year-old quarter horse which was evaluated due to a history of a right forelimb lameness of three weeks duration. Two and a half months later he presented again, this time for unilateral epistaxis and persistent right forelimb lameness. Radiography of the right elbow noted an increasingly irregular, periosteal response and osteolytic lesion of the right distal humeral condyle. At the time of the second presentation, nasosinal endoscopy identified a lobulated mass in the region of the ethmoid turbinates. Histopathology of this mass revealed an adenocarcinoma of nasal origin with metastasis to the lung, liver, and right humerus.